Let there be light: Regulation of gene expression in plants - Petrillo, Ezequiel (RNA Biol, 2015)
Gene expression regulation relies on a variety of molecular mechanisms affecting different steps of a messenger RNA (mRNA) life: transcription, processing, splicing, alternative splicing, transport, translation, storage and decay. Light induces massive reprogramming of gene expression in plants. Differences in alternative splicing patterns in response to environmental stimuli suggest that alternative splicing plays an important role in plant adaptation to changing life conditions. In a recent publication, our laboratories showed that light regulates alternative splicing of a subset of Arabidopsis genes encoding proteins involved in RNA processing by chloroplast retrograde signals. The light effect on alternative splicing is also observed in roots when the communication with the photosynthetic tissues is not interrupted, suggesting that a signaling molecule travels through the plant. These results point at alternative splicing regulation by retrograde signals as an important mechanism for plant adaptation to their environment.